Rewitalizacja miast jako program publiczny na przykładzie Niemiec w latach 1971-2000 = Revitalization of cities as a public program - the example of Germany between 1971 and 2000 - Billert, Andreas (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Revitalization of cities is a complex concept. In material (traditional) terms, it covers activities supporting the rehabilitation of ?outdated? spatial, functional, and building structures of city districts. Since the end of the 20th century, it has included also activities aimed at eliminating undesired socio-economic phenomena, such as social disintegration and marginalization, poverty, unemployment, and crime in city districts considered to be problematic or degraded. Both degradation and revitalization of city districts are often involved in, on the one hand, mechanisms of the private real estate market and, on the other, the political activities of public sector.
Keywords: rewitalizacja miasta; Niemcy; polityka miejska; prawo rewitalizacyjne; urban regeneration/revitalization; Germany; urban policy; revitalisation law